Clinical and epidemiological characteristics and factors associated with skin and soft tissue infection in military personnel (Salud, Arte y Cuidado, 2022)
The objective of the study was to determine the clinical and epidemiological characteristics and factors associated with abscessed cellulitis in military personnel. The study is descriptive with a quantitative approach of non-experimental design. The technique corresponds to a documentary observation by reviewing the medical records of the patients who were treated in the Internal Medicine service by IPPB. The results show that 98% presented an increase in volume, 93% presented pain, 90% redness, 80% heat and 50% fever, 62% of the patients were between 18 and 38 years of age, 77% were male, 77% from urban residences; traumatic wounds being the factor associated with the highest incidence with 42%, followed by insect bites 28%, with excoriations occupying third place, 17%, and IPPB associated with fungal infections, 4%. Regarding the associated factors, 12% were diabetic patients, 10% presented obesity, 5% with peripheral vascular disease, surgical wounds and immunosuppressed. It is concluded that a large percentage of patients presented clinical and epidemiological characteristics compatible with those described in the literature.
Keywords: abscess cellulite; clinical epidemiological